1990
DOI: 10.1056/nejm199001113220203
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Effects of Exposure to Low Doses of Lead in Childhood

Abstract: To determine whether the effects of low-level lead exposure persist, we reexamined 132 of 270 young adults who had initially been studied as primary school-children in 1975 through 1978. In the earlier study, neurobehavioral functioning was found to be inversely related to dentin lead levels. As compared with those we restudied, the other 138 subjects had had somewhat higher lead levels on earlier analysis, as well as significantly lower IQ scores and poorer teachers' ratings of classroom behavior. When the 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
472
1
16

Year Published

1991
1991
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,082 publications
(503 citation statements)
references
References 18 publications
9
472
1
16
Order By: Relevance
“…Toxicological . and clinical studies have established no lower thresh old for deleterious human health effects from lead Ž Needleman et al, 1979;McMichael et al, 1988;Needleman et al, 1990;Bellinger et al, 1991;. Bellinger et al, 1994 .…”
Section: Introductionmentioning
confidence: 99%
“…Toxicological . and clinical studies have established no lower thresh old for deleterious human health effects from lead Ž Needleman et al, 1979;McMichael et al, 1988;Needleman et al, 1990;Bellinger et al, 1991;. Bellinger et al, 1994 .…”
Section: Introductionmentioning
confidence: 99%
“…Of particular importance, exposure to low levels of lead in utero or in early childhood may lead to irreversible central nervous system damage (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…The homooctameric zinc metalloenzyme, 6-aminolevulinate dehydratase (porphobilinogen synthase, ALAD, EC 4.2.1.24), is the second enzyme in the heme biosynthetic pathway. ALAD is expressed in all tissues, but occurs at elevated levels in liver, which has the added burden of cytochrome P450 synthesis, and in the highest levels in erythrocytes and their precursors.…”
Section: Introductionmentioning
confidence: 99%
“…3-0.7 (White, 1982), and evidence has suggested that SES is predictive both of decoding single words and non-words, as well as reading comprehension (Bowey, 1995;Hecht et al, 2000;Raz & Bryant, 1990). Although SES is most commonly indexed using education, occupation, and income (Ensminger & Fothergill, 2003), many other factors vary systematically with SES (Barnett, 1998; BrooksGunn, Klebanov, & Duncan, 1996;Hawley & Disney, 1992;Jackson, Brooks-Gunn, Huang, & Glassman, 2000;Klein, Hack, & Breslau, 1989;Korenman, Miller, & Sjaastad, 1995;Leventhal & Brooks-Gunn, 2003b;McCormick, 1989;Needleman, Schell, Bellinger, Leviton, & Allred, 1990;Ramey & Ramey, 1998) and are likely to play a role in creating and sustaining the SES gap in cognitive performance and achievement (Bornstein & Bradley, 2003). For this reason the association between SES and reading ability is likely to be multifactorial.…”
mentioning
confidence: 99%
“…One child suffered a head injury involving loss of consciousness for several hours. Because physical and mental health factors could account for SES differences in cognitive performance (Hawley & Disney, 1992;Klein et al, 1989;McCormick, 1989;Needleman et al, 1990), analyses will be presented below both including and excluding children with medical or psychiatric histories. …”
mentioning
confidence: 99%